Penerapan Metode Bercerita Dengan Media Konkreat Untuk Meningkatkan Kemampuan Berbahasa Anak Usia Dini - Azizah, Azizah; Dewi, Harmala; Sulistiani, Tini; Asmara, Adi; Hidayat, Tomi (STIA Bengkulu, 2025)
This research aims to increase the student‘s speaking ability who learn at the preschool by using Telling Story with Concrete Media, in this case the author choose “Pineapple”. The authors believe by using concrete media the student’s speaking ability will improve. The subject of this research is the children are fifth until to sixth years, they are one class, it is class B. The school named TK Negeri Pembina Argamakmur. The data collect by documentation, interview and observation. The author use descriptive qualitative as the methodology and analyze data. This research consists of two cycles. At first cycle the author get fact that the student’s speaking ability is lacking, it is prove by the Interview. The student can not explain with detail what are information regarding “Pineapple”. They just give one word; it is prove by the trancript (result of interview (Figure 1)). After got the data the author gives the class treatment. It is Story Telling by using Concrete Media. The teacher entering “Pineapple” in the classroom and ask student to touch and eat”Pineapple”, after that the teacher explain detail information regarding “Pineapple”. After that entering Second Cycle in this stage the author gives Posttest, it is interview, the results show that the student’s speaking ability has improved than before. The students usemore than three sentence consist of more than three words in one sentence. It is proved by transcript (resul of interview (figure 2)). This is as the proven that “Media Concrete” in this research is Pineapple is the suitable technique to increase the student’s speaking ability.